Education and teaching Ead: reflections on pedagogical practice in Post Modernity - Santos Vieira , Edinilson; Araújo Leal, Débora (Seven Editora, 2023)
This article aims to discuss Education and Distance Learning, so it is taken into account that technology is a product of the Exact Earth and Applied Social Sciences that involves a set of instruments, methods and techniques aimed at improving the knowledge tree. As well as, Agrarian Sciences, Biological, Health, Engineering, Humanities, Linguistics, Letters and Arts which are practical applications of scientific knowledge in various areas of research and that assume great importance in human life, they provide increasingly modern tools, in various sectors, which provides convenience, entertainment, curiosity and fun. The purpose is to show how education has spread in conjunction with distance learning and electronics, however the student can count on an environment that wants to be with people from their own social life, or listen to music, in short, you can enjoy your day and still manage your studies, with "autonomy". This is a qualitative study with bibliographic research that points through literature and the confrontations of Post Modernity as THE is the new key for Education and the promotion of Hybrid and Remote Teaching.